2003
DOI: 10.1002/ffj.1272
|View full text |Cite
|
Sign up to set email alerts
|

Maturity discrimination of snake fruit (Salacca edulis Reinw.) cv. Pondoh based on volatiles analysis using an electronic nose device equipped with a sensor array and fingerprint mass spectrometry

Abstract: GC-olfactometry was used to characterize the specific aroma of a pentane extract of snake fruit (Salacca edulis Reinw cv. Pondoh). Ten compounds, including two carboxylic acids, six methyl esters, an alcohol and a furaneol (2,5-dimethyl-4-hydroxy-3(2H)-furanone), were detected as the most characteristic odorants. Methyl esters exhibited particularly sweet and fruity odour characteristics in snake fruit at more mature stages, whereas carboxylic acids exhibited the sweaty odour that tends to prevent non-native c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…E-nose devices have been successfully applied to different fields particularly in food and beverage industries, such as snake fruit (Supriyadi et al, 2004), tomato (Hernández Gómez et al, 2008), and coffee (Falasconi et al, 2005). E-noses have also been used for identification of tea grade (Yu et al, 2008), prediction of tea quality (Dutta et al, 2003b), and monitoring of black tea fermentation process (Bhattacharyya et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…E-nose devices have been successfully applied to different fields particularly in food and beverage industries, such as snake fruit (Supriyadi et al, 2004), tomato (Hernández Gómez et al, 2008), and coffee (Falasconi et al, 2005). E-noses have also been used for identification of tea grade (Yu et al, 2008), prediction of tea quality (Dutta et al, 2003b), and monitoring of black tea fermentation process (Bhattacharyya et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Parastar et al combined fingerprint analysis using GC–MS with chemometric to analyse secondary metabolites of citrus peels [17]. Fingerprint analysis using mass spectrometry and electronic nose based on sensors is also used for determination fruit maturity [18]. Previous reports show the difference in aroma of limequat and kumquat, what determines difference in their fingerprints [11].…”
Section: Resultsmentioning
confidence: 99%
“…Supriyadi et al found that electronic noses could detect and distinguish the different maturation periods of salak. (10) They also used a GC-odor detector to determine ten characteristic components that could influence odors and analyzed maturity-related changes in components by MS online analytical processing (OLAP) with the use of an electronic nose. Italian researchers Buratti et al (11) provided sensory descriptions of wines of different Italian brands by combining an electronic nose with a spectrophotometer.…”
Section: Electronic Nosesmentioning
confidence: 99%